Modern Developments of Griesbach's Hypothesis - Farmer, William Reuben (New Testament studies, 1977)
To refer to ‘modern developments’ of Griesbach's hypothesis makes clear that the present revival of interest in Griesbach's work is not simply an uncritical return to the past. For example, Griesbach accepted the traditional view of Augustine that Luke used Matthew even as he broke with tradition in affirming that Mark came after Luke as well as after Matthew. To the extent that Griesbach assumed Luke's use of Matthew while never discussing the relationship between those two gospels, his solution to the synoptic problem, for over a century and a half, remained in what must be judged as a critically undeveloped condition. Contemporary advocates of the Griesbach hypothesis have been obliged to explain the relationship of Luke to Matthew and in other ways develop a more convincing explanation of this hypothesis. This essay gives an account of the progress that has been made during the past twelve years in clarifying the merits of Griesbach's solution to the synoptic problem. In answering some of the objections that have been raised against this solution, an effort has been made to advance the discussion even further toward a more adequate resolution of this important question. The Epilogue includes some clarifying statements on the argument(s) from order.